2021
DOI: 10.3389/fcimb.2021.689197
|View full text |Cite
|
Sign up to set email alerts
|

Low-Abundant Microorganisms: The Human Microbiome’s Dark Matter, a Scoping Review

Abstract: Research on the human microbiome has mainly been restricted to the identification of most abundant microbiota associated with health or disease. Their abundance may reflect their capacity to exploit their niche, however, metabolic functions exerted by low-abundant microrganisms can impact the dysbiotic signature of local microbial habitats. This scoping review aims to map the literature regarding the management of low-abundant microorganisms in studies investigating human microbiome samples. A systematic liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 83 publications
5
30
0
Order By: Relevance
“…Bifidobacterium and other commensal gut microbiota can compete for nutrients with foodborne pathogens (Kamada et al, 2013;O'Callaghan and van Sinderen, 2016), which would further limit the ability for C. sakazakii to grow within the SHIME compartment. Despite the relatively low abundance of some gut microbiota, including Bifidobacterium, our results provide further evidence that the gut microbiota may play a significant biological role through synergistic interactions with other microorganisms (Claussen et al, 2017;Benjamino et al, 2018;Cena et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…Bifidobacterium and other commensal gut microbiota can compete for nutrients with foodborne pathogens (Kamada et al, 2013;O'Callaghan and van Sinderen, 2016), which would further limit the ability for C. sakazakii to grow within the SHIME compartment. Despite the relatively low abundance of some gut microbiota, including Bifidobacterium, our results provide further evidence that the gut microbiota may play a significant biological role through synergistic interactions with other microorganisms (Claussen et al, 2017;Benjamino et al, 2018;Cena et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…Whereas most 16S rRNA gene sequencing analyses only reliably classify taxa to the genus level and do not report species and strains usually. Using shotgun metagenomic sequencing, oral and gut bacterial communities show greater similarity than earlier studies suggested (de Cena et al, 2021;Maki et al, 2021). Moreover, diurnal variations, processing methods, race, and diet are irrelevant interference with measurement results, which requires further consideration in future studies (Superdock and Poole, 2022).…”
Section: Hematogenous Routementioning
confidence: 87%
“…Current research on the salivary microbiome has mainly been restricted to the identification of the most abundant microbiota associated with health or disease. We believe that this strategy could cause an incomplete misunderstanding of the ecology and environment as metabolic functions exerted by low-abundant microorganisms can be linked to the dysbiotic microhabitats in a sort of ‘butterfly effect’ [ 58 ]. This can be clearly observed by the inclusion of Desulfobulbus in the analysis, even at very low relative abundance.…”
Section: Discussionmentioning
confidence: 99%